Sensing Nature’s Pulse: On Relearning to Read the”‘Book of Nature” - Stevens, Catherine (Murmurations: Journal of Transformative Systemic Practice, 2024)
In recent years there has been a growing body of literature on nature based art therapies. Within this relatively new specialism there are a number of emerging models of environmental art therapy practiced by art therapists in the UK. Alongside this interest in the natural world, there is a growing awareness that for therapeutic practices to remain relevant in today’s world they need to recognise that we exist as a part of, and not apart from, nature and that humans are having a significant detrimental impact on the natural world as seen in the climate emergency, Bird (2023) and Deco (2021). The British Association of Art Therapist’s (BAAT) focused on this concern in their 2023 annual conference on the theme ‘Art therapy and the climate crisis.’ In writing this paper I seek to explore an area where I think art therapy would benefit from developing deeper reflections on the systemic nature of the ecological crises we face. The relationship between ourselves and the natural world necessarily involves ecological thinking such as Deep ecology, [a concept developed by the Norwegian philosopher Arne Naess (1990)], and the systemic thinking of Gregory Bateson (1972). Here I explore how, in taking my art therapy practice outdoors, (rather than the traditional art therapy studio) my therapeutic practice comes into immediate contact with the natural world, its dynamic rhythms, and its ecosystems. This makes it possible to develop a practice which is open to engaging in a dialogue between humans (therapist and clients) and the many other life forms, plants, animals, insects, etc. found in a garden.